EFEITO DA CARBONIZAÇÃO DA MADEIRA NA ESTRUTURA ANATÔMICA E DENSIDADE DO CARVÃO VEGETAL DE Eucalyptus - Bárbara Luísa Corradi Pereira; Ana Márcia Macedo Ladeira Carvalho; Aylson Costa Oliveira; Larissa Carvalho Santos; Angélica de Cássia Oliveira Carneiro; Mateus Alves de Magalhães (Ciência Florestal, 2016)
This study aimed to evaluate the anatomical changes that occur with charred wood and determine the anatomical properties, basic wood density and apparent density of charcoal Eucalyptus clones, besides elucidating the possible existing significant correlations. The scanning electron microscopy was performed in the transverse, longitudinal and tangential longitudinal and radial wood charcoal sections. In the morphological analysis of the pores and the apparent density was made. In general, the anatomical features such as pore radius and the wood fibers showed little or no change due to carbonization of coal surface and showed well defined structures. The changes in cellular elements of wood were mainly related to the quantitative parameters such as wall thickness and pore diameter fibers. The clones showed satisfactory basic density of wood for charcoal production. The anatomical parameters were significantly correlated with basic wood density and apparent density of charcoal, especially, in this study, the fraction of the fiber wall.